Senam Hamil sebagai Latihan Fisik pada Ibu Hamil di Wilayah Kerja Puskesmas Randudongkal Pemalang - Miskli Meilia, Triana; Daima Ulfa, Zuly; Nafiah, Ulin (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2024)
Pregnancy is physiological, but often in the third trimester, pregnant women had complaints of back pain. One of the exercises or stretches is pregnancy exercise. The research aims to analyze pregnancy exercise for back pain complaints. The research method is quasi-experimental with a one group pretest posttest design. The sample was pregnant women in the third trimester who complained of low back pain (18 people). Bivariate analysis to test the effectiveness of pregnancy exercise and prenatal yoga on back pain, was determined based on the normality test so that it used Wilcoxon. The results of the p-value analysis in the pregnancy exercise group was 0.000, which means there was effectiveness of pregnancy exercise for back pain, and in the prenatal yoga group it was 0.000 so that there was effectiveness of prenatal yoga for back pain in third trimester pregnant women. Pregnancy exercise is an optional exercise that are useful for reducing back pain which is often a complaint of third trimester pregnant women.